A Comparison of Alcohol Consumption Intentions Among Pregnant Drinkers and Their Nonpregnant Peers of Child-Bearing Age - Pettigrew, Simone; Jongenelis, Michelle; Chikritzhs, Tanya; Pratt, Steve; Slevin, Terry; Glance, D. (Informa Healthcare, 2016)
Objective: To investigate alcohol consumption intentions among Australian women of childbearing age by pregnancy status. Methods: Three national online surveys were conducted with adult drinkers who consume an alcoholic beverage at least two days per month. Data from female respondents of childbearing age were analyzed according to pregnancy status: pregnant (n = 101), possibly pregnant (n = 178), and not pregnant (n = 1,957). Results: Pregnant drinkers were significantly more likely than possibly pregnant and nonpregnant drinkers of child-bearing age to report that they should and will reduce their alcohol consumption. Results showed that 33% of the pregnant women, 32% of the nonpregnant women, and 39% of the possibly pregnant women reported intending to drink five or more standard drinks on a single occasion in the following two weeks. Older pregnant women exhibited higher rates of heavy drinking intentions and lower intentions to reduce their consumption relative to younger pregnant women. Conclusion: Despite current alcohol consumption guidelines recommending abstinence while pregnant, pregnant respondents exhibited heavy episodic drinking intentions comparable to those of their nonpregnant peers. Implications: There is a need to increase public awareness of current alcohol guidelines for pregnant women. Older women of childbearing age and those planning a pregnancy may require particular attention.